Household Consumption Volatility and Poverty Risk : Case Studies from South Africa and Tanzania - Bellon, Matthieu (IMF Working Papers; Working Paper ;, 2020)
Economic volatility remains a fact of life in Sub Saharan Africa (SSA). Household-level shocks create large consumption fluctuations, raising the incidence of poverty. Drawing on micro-level data from South Africa and Tanzania, we examine the vulnerability to shocks across household types (e.g. by education, ethnic group, and economic activity) and we quantify the impact that reducing consumption volatility would have on aggregate poverty. We then discuss coverage of consumption insurance mechanisms, including financial access and transfers. Country characteristics crucially determine which household-level shocks are most prevalent and which consumption-smoothing mechanisms are available. In Tanzania, agricultural shocks are an important source of consumption risk as two thirds of households are involved in some level of agricultural production. For South Africa, we focus on labor market risk proxied by transitions from formal employment to informal work or unemployment. We find that access to credit, when available, and government transfers can effectively mitigate labor market shocks.